Politics and Poetics of the Event: from silencing to a risk of voicing – - Romaguera (Universidade de Sorocaba – UNISO, Sorocaba/SP, Brazil), Alda Regina Tognini; Wunder (Universidade Estadual de Campinas – UNICAMP, Campinas/SP, Brazil), Alik (Revista Brasileira de Estudos da Presença, 2022)
Our interest is to think of politics and poetics of images and words in writings traversed by the experiences (workshops, soirées, exhibitions...) that have taken place in the extension and outreach project Reading and Creation Workshops with Words and Images developed by Fabulografias - ALB Center for Reading, throughout the years 2013 and 2014. How to extract the significance from words and photographs and make them vibrate, make them multiple? Launch the event in gatherings, thoughts and poetics and photographic compositions. One of the challenges of a plane of collective experimentation around the minority becoming, winds that blow in the meetings of the Collective Group Fabulografias. Among other things: doing away with the discursive orders and making life resonate from within a tense silence that drifts nearby. Compose an education that differs, blowing from within the potencies of art and the philosophy of Gilles Deleuze.